Study on Construction Response Characteristics of Large Cross-Section Tunnel Crossing Huge Karst Cave Backfill - Yunteng Chen; Yuancheng Cai; Jianwei Zhang; Jie Li; Xiaotong Huang; Hao Lei; Peilong Yuan (Shock and Vibration)
The existence of giant karst cave can cause collapse and water inrush hazards during the excavation of the karst tunnel, causing serious economic losses. In this paper, based on the FEA software MIDAS, a numerical simulation model for the backfilling of a large karst cave through a large cross-section tunnel was established. The distribution characteristics and change rules of the displacement field, stress field, horizontal support stress, and plastic zone of the tunnel surrounding rock and backfill were explored. The first stage of tunnel excavation leads to a sharp increase in the displacement of the tunnel’s surrounding rock and the deterioration of the plastic zone, which should be strengthened and monitored. The tunnel arch, waist, and wall footing areas were prone to stress concentration. The two layers of horizontal support force show a certain regularity, showing a sharp increase and a gradually smooth growth trend. Meanwhile, the site monitoring results for arch settlement and horizontal convergence of the mega cavern tunnel were analyzed. The results show that the numerical calculation results were in good agreement with the values of site monitoring data. The average errors of final crown settlement and horizontal convergence were 8.6% and 15.9%, respectively, which verified the correctness of the numerical modeling method. This project can provide reliable experience for the construction of similar large cavern tunnels.